Política e polícia: medidas de contenção de liberdade: modulações de encarceramento contra os jovens na sociedade de controle - Sebastião Júnior, Acácio Augusto (2009)
The police as a repressive institution that guarantees domestic peace adjusted with the military-diplomatic device to ensure external security of states is part of security in the modern reason of state, combining discipline and biopolitics. However, the police has not been restricted to a mere repressive function. According to Michel Foucault, it emerges as a government practice that watches over health and morality of a population inside a given territory. Politics and police. Measures for restraint of liberty: variations of imprisonment against youths in the society of control , departs from Foucault s genealogical analysis to establish a political history of the practices of restraint of liberty of children and youths. It does so in view of the changes in the technologies of power that renew police and politics in the society of control. The present research is interested in the battle carried out in Brazil, initially against those classified as in want, following by minors in irregular conditions and, today, those selected by punitive control and social assistance as children and adolescents in situation of risk. The contact with the application and evaluation of a project executing socio-educational measures in liberty, Pró-Menino of the Telefonica Foundation, allowed for an analysis of fluxes of restraints of liberty against youth classified as adolescents who committed an infraction (ato infracional). The government over children and adolescents reshape itself in new controls that intend to annul or moderate the potency of liberty of children and youth in the ever-stretching prison-building, in open-air concentration camps. The public-private partnership for the management of socio-educational measures currently resumes the police practice beyond its repressive expression, which is now extended to companies and NGOs. It is a restraint measure that targets children and youth, which were seen before as danger in the streets and currently perform the role of police of themselves in governed streets. Children and adolescents are not the future; they are in the present with their potencies of liberty and revolt